2015
DOI: 10.1007/s11661-015-3152-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties and Microstructure of Dissimilar Friction Stir Welds of 11Cr-Ferritic/Martensitic Steel to 316 Stainless Steel

Abstract: Dissimilar joints between ferritic and austenitic steels are of interest for selected applications in next generation fast reactors. In this study, dissimilar friction-stir welding of an 11 pct Cr ferritic/martensitic steel to a 316 austenitic stainless steel was attempted and the mechanical properties and microstructure of the resulting welds were examined. Friction-stir welding produces a stir zone without macroscopic weld-defects, but the two dissimilar steels are not intermixed. The two dissimilar steels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…Fine-grain refinement has influenced high hardness values between the SZ and Thermomechanical affected zone (TMAZ) of the F-M steel. 16 It is important to state that the 9Cr-1Mo-V-Nb steel similar welds need to be post-weld heat-treated to reduce the hardness of martensite formed in the weld metal and HAZ, to recover toughness and minimize detrimental residual stresses. 17 However, the post-weld heat treatment (PWHT) of dissimilar ferritic martensitic/austenitic weld configurations is very complex due to the location dependant compositional variations, carbon diffusion and softening, sensitization of austenitic stainless steel at the temperature range of PWHT, a significant loss in hardness in 9Cr-1Mo-V-Nb side HAZ.…”
Section: Introductionmentioning
confidence: 99%
“…Fine-grain refinement has influenced high hardness values between the SZ and Thermomechanical affected zone (TMAZ) of the F-M steel. 16 It is important to state that the 9Cr-1Mo-V-Nb steel similar welds need to be post-weld heat-treated to reduce the hardness of martensite formed in the weld metal and HAZ, to recover toughness and minimize detrimental residual stresses. 17 However, the post-weld heat treatment (PWHT) of dissimilar ferritic martensitic/austenitic weld configurations is very complex due to the location dependant compositional variations, carbon diffusion and softening, sensitization of austenitic stainless steel at the temperature range of PWHT, a significant loss in hardness in 9Cr-1Mo-V-Nb side HAZ.…”
Section: Introductionmentioning
confidence: 99%
“…This welding method has been applied to various structural materials with thorough studies, including Ti-6Al-4V titanium alloy, aluminum alloys, and Inconel alloy 600 [7][8][9]. FSW is applied to different kinds of alloys because of its special advantages, such as solid-state joining, no requirement for filler materials, and high feasibility of dissimilar welding [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…With the progress of welding technology and tool materials, a lot of researches have been conducted on dissimilar friction stir welding (DFSW) of steels, such as dissimilar carbon steels, [ 12–15 ] stainless steel and ferritic/martensitic steel, [ 10,16–19 ] stainless steel and carbon steel, [ 8,20–23 ] stainless steel and Ni‐based alloy, [ 24–26 ] and dissimilar stainless steels. [ 7,27–29 ] In similar FSW, the material on the advancing side (AS) experiences a higher strain rate, whereas the asymmetric material flow in the stirring zone (SZ) will cause the AS to experience a higher temperature and a greater degree of deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in the study of DFSW of F82H RAFM steel (harder than 304 ASS at ambient temperature) and SUS304 ASS (harder than F82H at welding temperature), Chung et al [ 10 ] recommended the process parameters that the F82H is on the AS and the tool pin is totally plunged on the F82H side, so that sound joint with no mixed structure and intermetallic compounds can be fabricated, and they found that during FSW, the bonding interface always shift from the SUS304 side toward the F82H side. In DFSW of 11Cr–ferritic/martensitic steel and 316 ASS, the experiments by Sato et al [ 19 ] revealed that void defect can be avoided by the parameters that locating the 11Cr steel on the RS and offsetting the tool to AS, and the metallic bonding is successfully achieved between the two steels, but no material intermixing occur in the SZ. Whereas, He et al [ 16 ] revealed that in the DFSW of RAFM and 316L ASS, the tool offset has little effect on the material flow, and the material flow can be improved by increasing the rotation speed.…”
Section: Introductionmentioning
confidence: 99%